2019
DOI: 10.1016/j.ijheh.2019.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Capacity building and training approaches for water safety plans: A comprehensive literature review

Abstract: The World Health Organization has recommended Water Safety Plans (WSPs), a holistic risk assessment and risk management approach, for drinking-water suppliers across low-, middle- and high-income countries, since publishing its 2004 Guidelines for Drinking-Water Quality. While rapid WSP adoption has occurred, capacity is still catching up to implementation needs. Many countries and regions lack case examples, legal requirements, and training resources for WSPs, corresponding to widespread capacity shortfall in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 56 publications
0
42
0
10
Order By: Relevance
“…External support is needed The dilemma analysis found that lack of empowerment creates barriers to improving water safety through monitoring. This is also reflected in the literature on water safety planning, which frequently highlights inadequate financing [34][35][36][37] and capacity 34,35,[38][39][40] as substantial barriers to successful implementation. In rural areas in particular, inadequate financing and capacity have meant that water safety planning efforts focus on the early stages of the approach (assembling a team, describing the water supply and identifying hazards, developing and implementing a plan for improvement) but neglect the latter stages of monitoring, verification, and iterative learning 33,39 , which are crucial to the effectiveness and sustainability of the approach 29,37 .…”
Section: Contextualising Monitoring Resultsmentioning
confidence: 98%
“…External support is needed The dilemma analysis found that lack of empowerment creates barriers to improving water safety through monitoring. This is also reflected in the literature on water safety planning, which frequently highlights inadequate financing [34][35][36][37] and capacity 34,35,[38][39][40] as substantial barriers to successful implementation. In rural areas in particular, inadequate financing and capacity have meant that water safety planning efforts focus on the early stages of the approach (assembling a team, describing the water supply and identifying hazards, developing and implementing a plan for improvement) but neglect the latter stages of monitoring, verification, and iterative learning 33,39 , which are crucial to the effectiveness and sustainability of the approach 29,37 .…”
Section: Contextualising Monitoring Resultsmentioning
confidence: 98%
“…Worldwide experience, including high-income countries, has shown that key success factors for WSP implementation include regulatory requirements for a risk-based approach, access to tools such as manuals and guidance, training resources, cooperation across the sector as in national platforms, and context-specific evidence of the feasibility and benefits of WSP ( Schmiege et al, 2020 ; Kayser et al, 2019 ; Ferrero et al, 2019 ; Baum and Bartram, 2018 ; Amjad et al, 2016 ; Baum et al, 2016 , Gunnarsdottir et al, 2012a & 2012b ). These factors are especially important for small systems where there are typically fewer skills and resources available.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the Asia–Pacific study, we employed primary and secondary data sources to systematically assess the status of the 20 WSPs and identify the main enablers and barriers that explain these audit scores. Even though audit scores may not be directly correlated to WSP outcomes and impacts [11], audit is a summative evaluation step that enables understanding knowledge application and synthesis [30]. This study serves as a benchmark for the assessment of WSP development and implementation in Africa, especially for water schemes serving small and large urban centers.…”
Section: Discussionmentioning
confidence: 99%